Action Research to Examine the Effects of Integrating Facebook, Twitter, and YouTube in Online Math Classes on Students’ Engagement - Abo-Alhija, Wejdan (Technium Social Sciences Journal, 2021)
This research was implemented to examine the effects of integrating Facebook, Twitter, and YouTube in online math classes on students’ engagement by correlating their formative assessment results. Thirty-three students of grade 11 and 12 were included in this research. The teacher presented math questions at an online math class and asked students to use Twitter and YouTube to look for answers and share their results on the math Facebook page. According to the formative assessment results, the students achieved higher results than before integrating Facebook, Twitter, and YouTube into online math classes. The interviews took place with students to determine students’ views about using Facebook, Twitter, and YouTube in online math classes. Their results were evaluated, classified, and discussed diverse essential considerations about integrating Twitter and YouTube into online courses. The effect of integrating Facebook, Twitter, and YouTube on students’ engagement and formative assessment results was investigated through students’ surveys, online interviews, and teacher observation.